2019
DOI: 10.1200/jco.18.02018
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Human, First-in-Class Phase I Trial of the Anti-CD47 Antibody Hu5F9-G4 in Patients With Advanced Cancers

Abstract: PURPOSE To evaluate the safety, pharmacokinetics, and pharmacodynamics of Hu5F9-G4 (5F9), a humanized IgG4 antibody that targets CD47 to enable phagocytosis. PATIENTS AND METHODS Adult patients with solid tumors were treated in four cohorts: part A, to determine a priming dose; part B, to determine a weekly maintenance dose; part C, to study a loading dose in week 2; and a tumor biopsy cohort. RESULTS Sixty-two patients were treated: 11 in part A, 14 in B, 22 in C, and 15 in the biopsy cohort. Part A used dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
359
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 452 publications
(366 citation statements)
references
References 17 publications
7
359
0
Order By: Relevance
“…66 Early clinical trials with CD47/SIRPα axis inhibitors have shown promising activity in B-cell lymphoma and some solid tumors. [40][41][42]66 Our findings, demonstrating frequent expression of CD47 in many sarcomas, suggest that targeting the CD47/SIRPα axis in these tumors may be worthwhile, for example, in chordoma and dedifferentiated liposarcoma. However, it should be noted that some relatively common sarcoma types (including leiomyosarcoma, undifferentiated pleomorphic sarcoma, and Ewing sarcoma) expressed CD47 infrequently, reiterating the potential for false-negative results when trials lump together different soft tissue sarcomas.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…66 Early clinical trials with CD47/SIRPα axis inhibitors have shown promising activity in B-cell lymphoma and some solid tumors. [40][41][42]66 Our findings, demonstrating frequent expression of CD47 in many sarcomas, suggest that targeting the CD47/SIRPα axis in these tumors may be worthwhile, for example, in chordoma and dedifferentiated liposarcoma. However, it should be noted that some relatively common sarcoma types (including leiomyosarcoma, undifferentiated pleomorphic sarcoma, and Ewing sarcoma) expressed CD47 infrequently, reiterating the potential for false-negative results when trials lump together different soft tissue sarcomas.…”
Section: Discussionmentioning
confidence: 67%
“…In phase 1 studies targeting CD47/ SIRPα signaling, encouraging responses were seen in both lymphoma and advanced solid tumors. [39][40][41][42] Overexpression of CD47 has been observed across most cancers, [32][33][34][35][36][43][44][45] including in osteosarcoma, 46 but has never been systematically examined in soft tissue sarcomas.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that CD47 blockade promotes macrophage reprogramming, which drives macrophage phagocytosis of cancer cells in xenograft mouse models [180,181]. Hu5F9-G4 and CC-90002 are CD47 antibodies that are currently being studied in phase I clinical trials with promising results [182]. TTI-621, a recombinant protein that blocks the CD47-SIRPα signaling in humans, is currently being studied in clinical trials including multiple solid tumors based on previous xenograft studies where it improved macrophage phagocytosis of cancer but not normal cells [183].…”
Section: Tumor-associated Macrophages As Immunotargets and Their Potementioning
confidence: 99%
“…Several molecules targeting CD47/SIRPa axis are being developed as therapeutic agents for treatment of different tumor types (Table 1). However, initial data from phase 1 trials are not as promising as the preclinical data suggested [80].…”
Section: Boosting the Antitumoral Effects Of Macrophages By Tam Repromentioning
confidence: 99%